A Game-Based Nutrition Education Model for Elementary School Students in Stunting-Prone Areas - Wahyu Indah Dewi Aurora; Ahmad Syauqy; Andika Sulistiawan; Mirna Marhami Iskandar; Armaidi Darmawan; Erny Kusdiyah (Universitas Pendidikan Ganesha, 2026)
Stunting remains a critical issue that constrains children's physical growth and cognitive development. Limited nutritional literacy among elementary school students further reinforces unhealthy eating behaviors that persist over time. This study aims to analyze, develop, and validate a structured game-based nutrition education model to enhance students’ understanding of nutritional concepts. This research employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects consisted of 100 elementary school students in grades III–V, classroom teachers, and three expert validators specializing in nutrition, public health, and instructional design. Data were collected through needs analysis questionnaires, expert validation instruments, classroom observations, and student and teacher response questionnaires. Data analysis was conducted using the Content Validity Index (CVI) and descriptive statistics. The findings indicate that the developed model demonstrates high validity (CVI = 0.89) and effectively improves students’ engagement, motivation, and conceptual understanding of nutrition. Teachers also reported that the model is practical, adaptable, and supports active learning. Therefore, the game-based nutrition education model is considered valid and feasible for implementation as an educational intervention strategy to prevent stunting. The study implies the importance of integrating innovative learning approaches into nutrition education at the elementary level.